How psychedelic-assisted therapy works for depression: expert views and practical implications from an exploratory Delphi study - Johansen, Lauren; Liknaitzky, Paul; Nedeljkovic, Maja; Murray, Greg (Frontiers in Psychiatry, 2023)
As investigations into the efficacy of psychedelic-assisted psychotherapy to treat depression continue, there is a need to study the possible mechanisms of action that may contribute to the treatment's antidepressant effects. Through a two-round Delphi design, the current study investigated experts' opinions on the psychological mechanisms of action associated with the antidepressant effects of psychedelic-assisted psychotherapy and the ways such mechanisms may be promoted through the preparation, dosing, and integration components of treatment. Fourteen and fifteen experts, including both clinical psychedelic researchers and therapists, participated in Round 1 and Round 2 of the study, respectively. Thematic analysis identified nine important or promising 'mechanistic themes' from Round 1 responses: psychological flexibility, self-compassion, mystical experiences, self-transcendence, meaning enhancement, cognitive reframing, awe, memory reconsolidation and ego dissolution. These mechanisms were presented back to experts in Round 2, where they rated 'psychological flexibility' and 'self-compassion' to be the most important psychological mechanisms in psychedelic-assisted psychotherapy for depression. Strategies or interventions recommended to promote identified mechanisms during the preparation, dosing, and integration components of treatment were nonspecific to the endorsed mechanism. The findings from this study provide direction for future confirmatory mechanistic research as well as provisional ideas for how to support these possible therapeutic mechanisms.